KEMATANGAN EMOSI MAHASISWA DALAM MENYELESAIKAN SKRIPSI: SEBUAH STUDI KEPUSTAKAAN - Errika Maulidha E; Mohammad Salehudin (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2021)
Thesis is a scientific work made to meet the requirements of a student in completing an undergraduate program. In short, according to some literature emotional maturity is the ability to think realistically, can accept all the facts that exist in him, be able to channel his energy well, and be able to control his emotions well. The purpose of this research is to find out about the importance of emotional maturity for final year students in completing their thesis. This research is also expected to provide benefits in the future, can be used as reference material for further research, and can help the public and students to find out about the importance of having stable or high emotional maturity. The method used in this research is a qualitative approach with the type of literatur research (library), or better known as library research. From the results of these studies it can be concluded that emotional maturity is very much needed for students who are at the final level in doing thesis writing assignments.